A simple model of an oil based global savings glut: the China factor and the OPEC cartel - Ansgar Belke; Daniel Gros (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The purpose of this contribution is to illustrate the mechanism by which higher oil prices might lead to lower interest rates in the context of a simple model that takes into account the global external savings equilibrium. The simple model has interesting implications for how one views the huge US current account deficit and how the emergence of China's savings surplus and oil supply shocks impact the global economy. We show that the new equilibrium is located at a lower interest rate but also at a lower growth rate than without the China effect. Moreover, we argue that the lower real interest rates resulting from excess OPEC savings have facilitated the adjustment to the subprime crisis.
Keywords: E21; E43; F32; Q43; 330; China factor; current account adjustment; interest rate; oil prices; saving glut; Erdölpreis; Zins; Sparquote; Leistungsbilanz; USA; China